2013
DOI: 10.1128/jcm.00589-13
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Carriage of Klebsiella pneumoniae and Other Gram-Negative Bacilli in Pneumonia-Prone Age Groups in Semarang, Indonesia

Abstract: Gram-negative bacilli (GNB) cause many cases of pneumonia in Indonesia. We investigated nasopharyngeal carriage of GNB in Semarang, Indonesia. Klebsiella pneumoniae carriage in adults (15%) was higher than in children (7%) (P ‫؍‬ 0.004), while that of other GNB was comparable. Poor food and water hygiene are determinants of carriage of these bacteria.W orldwide, Streptococcus pneumoniae is the most common cause of community-acquired pneumonia (CAP). However, in low-to-middle-income countries, Gram-negative bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 9 publications
(4 reference statements)
7
40
3
1
Order By: Relevance
“…The correlation between alcohol consumption and K. pneumoniae carriage has also received little prior attention. The K. pneumoniae oropharyngeal carriage rate of 14.1% is comparable to the nasopharyngeal carriage rate of 11% determined by a recent study in Indonesia [17]. The rate of carriage of 1.6% (95% CI 0–5.1%) in children is also comparable to a study that reported a carriage rate of 1.4% amongst children aged less than 5 years attending daycare in Brazil, an upper-middle income country (The World Bank 2013) [18].…”
Section: Discussionsupporting
confidence: 80%
“…The correlation between alcohol consumption and K. pneumoniae carriage has also received little prior attention. The K. pneumoniae oropharyngeal carriage rate of 14.1% is comparable to the nasopharyngeal carriage rate of 11% determined by a recent study in Indonesia [17]. The rate of carriage of 1.6% (95% CI 0–5.1%) in children is also comparable to a study that reported a carriage rate of 1.4% amongst children aged less than 5 years attending daycare in Brazil, an upper-middle income country (The World Bank 2013) [18].…”
Section: Discussionsupporting
confidence: 80%
“…The characteristics of the participants have been presented previously [4]. Crowding was common, as was exposure to smoke.…”
Section: Resultsmentioning
confidence: 99%
“…1,18,19 The high prevalence of K. pneumoniae and other GNB might, in part, be explained by the common carriage of these bacterial species in the nasopharynx of healthy individuals in the same area. 20 The tropical climate with higher temperature and humidity in Semarang may increase the incidence of GNB infection, as those conditions promote the growth and virulence of GNB. 21,22 S. pneumoniae infection was detected in only 13% of the patients, mostly by urinary antigen tests.…”
Section: Discussionmentioning
confidence: 99%